Semiotic insights on the socio-cultural influence of the San Sebastian Church architectural facade, Lumban, Laguna, Philippines - Ronald Allan S. delos Reyes; Jomel Paulo G. Ebron; Jhona N. Gamez; Christie C. Amores; Ma Rovilla C. Sudaprasert (Social Sciences and Humanities Open)
The architectural styles found in the Philippines definitely belong to the Western sphere of influence. This might seem remarkable as the country is placed geographically at the most eastern flank of the SouthEast Asian region facing the center of the Far Eastern dominions. This study investigates this architectural trait and presents its impact on the formation of the self-identity of Filipinos. From documents that are gathered, it has been found that the Philippines has had a very active interchange both economically and culturally dating back to Roman times with the Western Hemisphere. These interactions have paved the way in the expeditious construction of churches and cathedrals once Spanish rule was established in the 16th century. One of the starting points of this building program was the San Sebastian Church in the town of Lumban, Laguna, the first to be built outside of Manila in Luzon. Through semiotic analysis, the meanings of the symbols and designs found in San Sebastian Church have been corroborated to have played a role in the formation of the values and norms of the people indicating that spirituality and religion are significant facets of the human persona. This study explored the semiotic significance of architectural and artistic elements within San Sebastian Church in Laguna. Through a survey and analysis, it was revealed that these symbols evoke a range of emotions and interpretations beyond purely religious connotations.